2017
DOI: 10.1074/jbc.m116.764407
|View full text |Cite
|
Sign up to set email alerts
|

CDK5/FBW7-dependent ubiquitination and degradation of EZH2 inhibits pancreatic cancer cell migration and invasion

Abstract: Pancreatic cancer is one of the most lethal cancer types. Enhancer of zeste homolog 2 (EZH2) is an oncogenic protein overexpressed in pancreatic cancer, and EZH2 could be a potential therapeutic target for the treatment of pancreatic cancer. Although significant progress has been made toward understanding the function and deregulation of EZH2 in cancer cells, the posttranslational regulation of EZH2 in cancer cells is still unclear. F-box and WD repeat domain-containing 7 (FBW7) acts as a tumor suppressor by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 35 publications
2
76
0
Order By: Relevance
“…Several ubiquitin ligases promote EZH2 ubiquitination and degradation (Jin et al, 2017; Sahasrabuddhe et al, 2015; Yu et al, 2013). Destabilization of EZH2 by targeting its deubiquitinase may offer an alternative therapeutic approach to treating EZH2-overexpressing tumors, such as TNBC and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ubiquitin ligases promote EZH2 ubiquitination and degradation (Jin et al, 2017; Sahasrabuddhe et al, 2015; Yu et al, 2013). Destabilization of EZH2 by targeting its deubiquitinase may offer an alternative therapeutic approach to treating EZH2-overexpressing tumors, such as TNBC and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination is reversed by deubiquitinating enzymes (DUBs, or deubiquitinases), a group of proteases that remove monoubiquitin or poly-ubiquitin chains from the substrate (Wilkinson, 1997; Xiao et al, 2016). EZH2 protein is subject to ubiquitin-dependent degradation by several E3 ligases, including β-TrCP, SMURF2, and FBW7 (Jin et al, 2017; Sahasrabuddhe et al, 2015; Yu et al, 2013); however, the deubiquitinase that reverses this ubiquitination is unknown. Here we identify an ovarian tumor protease (OTU) family member, ZRANB1 (also known as Trabid), as an EZH2 deubiquitinase and a potential therapeutic target in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin modification is controlled by the opposing actions of E3 ligases and deubiquitinases to add or remove ubiquitin, respectively. Ubiquitination regulators are deregulated in PDAC, including tumor suppressors FBXW7 and USP9X (Pérez-Mancera et al 2012;Jin et al 2017), and potential oncogenes TRIM31 and RNF13 Yu et al 2018). Our analysis of PDAC genomic data revealed frequent amplification (22%) of the protein deubiquitinase USP21, prompting exploration of its potential role as an oncogene for PDAC.…”
mentioning
confidence: 80%
“…Ubiquitylation is considered to be an important modification of nuclear and cytoplasmic proteins at the post-translational level, as it is known that ubiquitylation serves an important function in cell apoptosis, cell cycle and dNA damage repair (24,25). A number of studies have demonstrated that ubiquitylation is strongly associated with the initiation and progression of carcinogenesis (26,27). Notably, numerous ubiquitin-associated proteins have been revealed as tumor suppressors/oncogenes and therapeutic targets in different tumor types (28,29).…”
Section: Scutellarein Inhibits the Development Of Colon Cancer Via CDmentioning
confidence: 99%